2009
DOI: 10.1093/nar/gkp088
|View full text |Cite
|
Sign up to set email alerts
|

Strand selective generation of endo-siRNAs from the Na/phosphate transporter gene Slc34a1 in murine tissues

Abstract: Natural antisense transcripts (NATs) are important regulators of gene expression. Recently, a link between antisense transcription and the formation of endo-siRNAs has emerged. We investigated the bi-directionally transcribed Na/phosphate cotransporter gene (Slc34a1) under the aspect of endo-siRNA processing. Mouse Slc34a1 produces an antisense transcript that represents an alternative splice product of the Pfn3 gene located downstream of Slc34a1. The antisense transcript is prominently found in testis and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 45 publications
3
42
0
Order By: Relevance
“…It has been shown that the sense/antisense dsRNA pairs in vertebrates are processed in the nucleus but not the cytoplasm [67,68]. Therefore, some plant nat-siRNAs may also be produced in the nucleus before introns are spliced out from the NATs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the sense/antisense dsRNA pairs in vertebrates are processed in the nucleus but not the cytoplasm [67,68]. Therefore, some plant nat-siRNAs may also be produced in the nucleus before introns are spliced out from the NATs.…”
Section: Discussionmentioning
confidence: 99%
“…19,24,28,29 The fact that these NATs share complementarity with their cognate mRNAs 3033 make the related piRNAs and endo siRNAs perfect guides to target effector complexes to protein-coding transcripts. We propose that sense–antisense hybrid formation and germ cell–specific RNA interference represent key events in the genomic quality-control mechanism that is essential to mitigating the consequences of enhanced transposition.…”
Section: Improving Selection Filters: Optimizing Part 2 Of the Evolutmentioning
confidence: 99%
“…Alternatively, antisense transcripts may instead block the translation of the sense mRNAs without changing the levels of the latter (21,22). It has been known that antisense transcripts are highly expressed in the testis, particularly in haploid cells (23,24). Therefore, antisense transcripts are likely active regulators of gene expression during spermatogenesis.…”
mentioning
confidence: 99%